Effects of ultrasonic treatment and current pulse frequency on properties of micro-arc oxidation coating on Mg alloy LAZ931 - Yishun Tian; Di Mei; Zhipeng Liu; Shuhao Xu; Jiayin Zhao; Haitao Xie; Jinxue Liu; Yang Xiao; Shijie Zhu; Shaokang Guan (Corrosion Communications)
To enhance corrosion resistance of magnesium-lithium (Mg-Li) alloy LAZ931 in corrosive environments, a micro-arc oxidation (MAO) based surface treatment was carried out under a unipolar pulsed power supply. Effects of ultrasonic treatment and current pulse frequency on the performance of MAO coatings were investigated using scanning electron microscopy, electrochemical characterization, and friction wear tests. Results demonstrate that ultrasonic treatment greatly reduced the number density of micro-defects in the resulting MAO coatings and improved their overall performance. Corrosion and wear resistance of the MAO coating increased when current pulse frequency increased from 400 to 2000 Hz. Those findings are beneficial for improving the performance of MAO on Mg-Li alloys through optimizing the processing parameters.